Use of correctional technologies in the process of health-recreational fitness training by men with impaired biogeometric profile of posture - Vitaliy Kashuba; Yuliya Rudenko; Tamara Khabynets; Natalia Nosova (Nicolaus Copernicus University in Toruń, Poland - University Sports Center, 2020)
The purpose of the article is to study the effectiveness of correctional technology applied for impairment of biogeometric profile of posture observed among mature men in the process of their health-recreational fitness training. Objective. In general, the number of respondents involved in the sequential transformation phase of the experiment comprised of n = 50 people, i. e. men in the second period of their adulthood (35 - 45 years). Methods. The paper uses the data gained from the analysis of professional scientific and methodological literature, pedagogical observation; functional assessment of movements; analysis of men's posture was performed using the "Torso" program, visual screening of the biogeometric profile of posture, methods of mathematical statistics. Results of the study. The paper presents a theoretical generalization as well as it offers a new solution to the scientific task, which presupposes development and scientific substantiation of correctional technology, applied for impairment of biogeometric profile of posture observed among men of the second period of their adulthood in the process of their health-recreational fitness training, all together aiming at improving general health. The author's technology consisted of three stages, in which physical activity was strictly regulated. The letter was determined on the basis of diagnosing the state of men's posture biogeometric profile. Among the criteria for the effectiveness of the author's technology the following ones should be noted, including the type of posture, the level of biogeometric profile of posture, the level of movements functional assessment, indicators of physical development, as well as physical fitness level of men aged 36 - 45 years. Conclusions. The results of a consistent transformation experiment have confirmed the effectiveness of the developed technology when it is used for correction of impaired biogeometric profile of the posture observed among men in the second period of their adulthood during their fitness training process. During the study the effectiveness of the author's technology was experimentally confirmed, which in its turn served as a basis for recommending it for practical use in the process of health-recreational fitness training by mature men. The framework of this work does not reduce the scientific potential of the chosen issue, and therefore the prospect of further research is to introduce and study the effectiveness of a differentiated approach to health-recreational fitness training by mature women given the level of biogeometric profile of their posture.